The usefulness of hybrid platform meetings for research ethics committees review meetings. (April 2022) - Shivananda, S.; Doddawad, Vidya Gowdappa
Highlights: This article will provide the glimpse on the difficulties in conducting the regular ethical review meeting due to covid restrictions. This article shall briefly discuss the applications, advantages and disadvantages of having hybrid mode of ethical review meetings. This article discusses various types of virtual meeting platforms that are suitable for conducting hybrid mode of ethical review meetings.